LISTENING MADE FUN: HOW SHORT ENGLISH CARTOONS ENHANCE YOUNG LEARNERS’ COMPREHENSION - Eka Putri, Zifa; Nuriska Cahyanti, Dian; Aida, Nida; Hidayani, Selnistia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to examine how short English cartoon media enhance elementary school students' listening skills, addressing a research gap where previous studies primarily focused on motivation rather than measurable listening performance. This study adopts an embedded mixed-method design, collecting quantitative data via 10-item multiple-choice pre- and post-listening tests, and qualitative data from semi-structured interviews. The study involved 26 fifth-grade students at Curug State Elementary School, Serang, Banten. Learners received a cartoon video-based treatment using age-appropriate content such as Dora the Explorer and Peppa Pig. Quantitative results show an increase in average scores from 34.62 (pre-test) to 78.46 (post-test). Qualitative findings reveal that students comprehend material better through video than audio alone, gain new vocabulary, and are more enthusiastic due to the combination of audio, visuals, and on-screen text. These findings support the Cognitive Theory of Multimedia Learning and Dual Coding Theory, affirming the importance of multimodal approaches for young English learners. Overall, short cartoons are shown to be an effective and enjoyable method to boost listening comprehension and learner motivation. ABSTRAK Penelitian ini bertujuan untuk menguji bagaimana media kartun Bahasa Inggris pendek meningkatkan keterampilan mendengarkan siswa sekolah dasar, mengatasi kesenjangan penelitian di mana penelitian sebelumnya terutama berfokus pada motivasi daripada kinerja mendengarkan yang terukur. Penelitian ini mengadopsi desain metode campuran tertanam, mengumpulkan data kuantitatif melalui tes pilihan ganda 10-item sebelum dan sesudah mendengarkan, dan data kualitatif dari wawancara semi-terstruktur. Penelitian ini melibatkan 26 siswa kelas lima di Sekolah Dasar Negeri Curug, Serang, Banten. Pembelajar menerima perawatan berbasis video kartun menggunakan konten yang sesuai dengan usia seperti Dora the Explorer dan Peppa Pig. Hasil kuantitatif menunjukkan peningkatan skor rata-rata dari 34,62 (pra-tes) menjadi 78,46 (pasca-tes). Temuan kualitatif mengungkapkan bahwa siswa memahami materi lebih baik melalui video daripada audio saja, memperoleh kosakata baru, dan lebih antusias karena kombinasi audio, visual, dan teks di layar. Temuan ini mendukung Teori Kognitif Pembelajaran Multimedia dan Teori Pengodean Ganda, yang menegaskan pentingnya pendekatan multimoda bagi pelajar bahasa Inggris muda. Secara keseluruhan, kartun pendek terbukti menjadi metode yang efektif dan menyenangkan untuk meningkatkan pemahaman mendengarkan dan motivasi belajar.